DINAMIKA AKTOR POLITIK DALAM MERESPONS TUNTUTAN FORUM PERJUANGAN DRIVER PARIWISATA BALI TERHADAP KEBIJAKAN IDENTITAS PENGEMUDI TRANSPORTASI ONLINE PEMILIK KTP LUAR BALI - Michael Gabriel; Piers Andreas Noak; Tedi Ervianto (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study examines the political actors’ responses to the demands of the Forum Perjuangan Driver Pariwisata Bali (FPDPB) regarding the policy of driver identity regulation for online transportation in Bali. Using a qualitative approach with a case study method, data were collected through in-depth interviews with members of the Bali Provincial Parliament (DPRD), technical staff from the Provincial Department of Transportation, and representatives of FPDPB. The findings indicate that the policy-making process reflects the dynamic interaction between local government and civil society, where FPDPB actively advocates for local drivers’ interests amid competition with non-local drivers. The Bali DPRD responded positively but faced bureaucratic challenges during the drafting of the regional regulation. Viewed through the lens of political pluralism theory, the process shows negotiation among multiple interests rather than domination by a single actor. The study concludes that political responses were accommodating yet constrained by administrative procedures, highlighting the need for better coordination and a clearer regulatory framework.